PEMANFAATAN MINYAK ATSIRI Litsea elliptica Blume PADA SEDIAAN SABUN CUCI TANGAN DI KELURAHAN DUREN SAWIT JAKARTA TIMUR - PRA PANCA BAYU CHANDRA; IKA AGUSTINA; TRIA PRAYOGA (Jurnal Pengabdian IKIFA, 2024)
Litsea is a plant that belongs to the Lauraceae family with 45 genera and more than 2,000 species. A total of 38 types of Litsea are known to grow in the Kalimantan region, including Litsea elliptica. Litsea elliptica is reported to have a dominant distribution in East Kalimantan. The aim of the Community Service (PkM) activities in Duren Sawit Subdistrict is to educate the public about the use of Litsea elliptica Blume Essential Oil in hand washing soap preparations. The PkM activity was attended by 45 residents from various areas in Duren Sawit Village. The results of the PkM activities showed an increase in respondents' knowledge about the use of Litsea elliptica Blume Essential Oil in hand washing soap preparations.